Target registration error reduction for percutaneous abdominal intervention. (January 2021) - Bas, Mateusz; Król, Krzysztof; Spinczyk, Dominik
Graphical abstract: Highlights: Spatio-temporal correspondence between the position before and during treatment of the target point was found The breathing phase selection is based on minimizing the TRE error in III-tier registration circuits. The deformation has been modeled using Elastic Body Spline. Differential Evolution methods was used to find optimal values of Elastic Body Spline parameters. The presented method works in real time. Abstract: A real-time methodology that finds spatio-temporal correspondence between the positions of the target point in the pre-treatment 3DCT image and during the procedure was proposed. It based on minimizing the target registration error in III tier registration circuits. Particle Swarm Optimization and Differential Evaluation were used to find optimal values of Elastic Body Spline parameters in the generation of abdominal deformation field. Different transformation classes have been tested: rigid, affine, Thin Plate Spline, Elastic Body Spline. The lowest TRE was obtained for the swarm optimization algorithm - differential evolution for the rigid and affine version: 3.47 and 3.73 mm, respectively.